The effects of social media on the mental health of collegiate male athletes - Halliburton, Jazsmin (Kansas State University, 2024)
The purpose of this thesis report is to research how social media is related to mental health in male student athletes focusing on the two most popular sports in the United States: football, and men’s basketball at the collegiate level. The popularity of men’s sports is more prominent than women’s sports, which is way male athletes are the focus for this research. This study is guided by the theoretical framework of framing and uses and gratification. The method of elite interviewing was used with the three division I male athletes participating with in the research. Research suggests athletes may be more likely to downplay or minimize the severity of their own mental health issues. In using the method of elite interviewing of the three former student athletes interviewed, only one said that he has experienced anxiety due to comments made about him by fans on social media platforms. One athlete is not mentally affected by the comments of fans and media due to where he grew up. The third athlete never experienced hurtful comments directed towards him, therefore, he was never mentally affected. Recommendations for future research in this topic would be a higher volume of research participants. An additional recommendation would be research into the discussion of mental health in the Black community, due to a majority of men’s football and basketball players being Black.
Keywords: Mental health; Athletes; Framing; Uses and gratification; Elite interviewing